Surgical Enucleation of a Dentigerous Cyst in a 12-Year-Old Child: A Case Report - Jha, Sweta; Koirala, Bandana; Dali, Mamta; Shrestha, Sneha; Poudel, Kabiraj; Keshwar, Shashi (Journal of Nepalese Association of Pediatric Dentistry, 2020)
Dentigerous cysts are the benign odontogenic cysts that surround the crown of an unerupted or impacted tooth and they account for approximately 20-24% of the jaw cysts. Dentigerous cysts involving impacted second premolars are rare. Here we report a case of surgical enucleation of an inflammatory type of dentigerous cyst associated with the impacted mandibular second premolar in a 12-year-old child. Nine-months follow up showed satisfactory healing of the defect with remarkable bone formation.